Assess the Bottom Sediment Quality of the Saigon River and its Tributaries in Binh Duong Using an Artificial Neural Network - Hien Than, Nguyen; Thi Anh Thu, Tran; Trong Dieu Hien, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 3, 2025)
Assessment of bottom sediment quality is vital in water resources management. The study collected sediment data at five monitoring stations in the Saigon River and its tributaries from 2013 to 2023. These monitoring data was used to construct our feedforward neutral network (FFNN) model. The model’s accuracy is 95.5% in assessing sediment quality. The study also presents a speedy method for evaluating the quality of bottom sediments in Vietnam.